PENGARUH VARIASI TEMPERATUR PIROLISIS TERHADAP KADAR HASIL DAN NILAI KALOR BRIKET CAMPURAN SEKAM PADI-KOTORAN AYAM - Saparudin, S.; Syahrul, S.; Nurchayati, N. (Universitas Mataram, 2015)
Energy is vital necessity as can not free on our daily. In a row inhabitant growth and economic development, the will necessity energy fuel oil (BBM) every years direct advance, until reseve fossil energy in the suppose quickly will finished. In the side other, increase the production well of agriculture sector although animal husbandry will the appear dirty area issue, because increase the waste as not used to well, the until necessary solution other enegy alternative. Biomass of the rise husk and chicken feces the have potential as high enough for in manner fuel become, be choosen that is briquettes, because the secondly this is waste be haved element contens carbon end course fiber as hight enough. Biomass briquettes this experiment in the difference become biocharcoal briquettes by pyrolysis process with the temperature variation 225°C, 275°C, 325°C and 375°C. The testing of experiment this is content result testing and calorofic value in the contents from temperature variation. The result of this experiment show that, the bigger of the pyrolysis temperature which is used the precentage of charcoal will be lower. The result of testing calorofic value briquetess biocharcoal the biggest that is 4252,67 kal/gr in the show on 275°C temperature the while, for lower calorofic value 3821,33 kal/gr on 225°C temperature. Of the calorofic value and as result, briquettes biocharcoal of the rice husk mixture with chicken feces the haved potential to growth as alternative fuel, be side energy contens as high enough, the material cheap and can easy.